Improvement of technology and mechanization means for weed control - M. M. Abdulgalimov; F. M. Magomedov; S. E. Sen'kevich; R. D. Umarov; I. M. Melikov (Сельскохозяйственные машины и технологии)
Weed vegetation in orchards and vineyards is one of the main reasons of low productivity. The applied technologies and weed control means provide decrease in contamination of orchards and vineyards insufficiently effectively that leads to a fruits harvest redice. Therefore it is necessary to improve the available methods and means, to develop new ones and on this basis to create scientifically-grounded complex of measures on weed control. This problem drequires further studies with the aim of developing the prospective technologies and technical means of mechanization for the weed control. Results of researches on mechanization of weed control, ways and means for realization of it are presented in the paper. Taking into account biological features of weeds the design of a flame cultivator for weed control in orchards and vineyards is developed and science-based. This cultivator will allow to reduce the prime cost, significantly increase quality and minimize the negative impact of herbicide use on crops, to improve yields, product quality and resource efficiency. Use of the offered flame cultivator will eliminate hand-weeding and help for more effective weed control in the rows of orchards and vineyards.